Periventricular Nodular Heterotopia and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 2006)
The clinical, MRI, and EEG findings in 54 patients (35 female, 19 male; aged 1 to 64 years) with periventricular nodular heterotopia (PNH) were analyzed in relation to epileptic outcome and genesis of epileptic discharges, in a study at the Neurological Institute and Epilepsy Surgery Center, Niguarda General Hospital, Milan, Italy.